Respostas Ecofisiológicas de Genótipos de Coffea Ssp. em Ambientes Contrastantes de Luminosidade: Pleno Sol X Sombreado - Borges, Alexandre Morais (2024)
Assessing the level of genetic dissimilarity that exists in any crop is critical to understanding the significant implications for variety selection and development. The objectives of the present study were to determine the variations between the genotypes of Coffea arabica and Coffea canephora subjected to different cultivation environments, for this purpose, the biometric characteristics, leaf attributes, chlorophyll index and transient fluorescence of chlorophyll a were evaluated in genotypes established in the North of Espírito Santo, in full sun cultivation environments and intercropped with rubber trees. Principal component analysis (PCA) demonstrated a tendency for genotypes to cluster in relation to the cultivation environment, showing that the light factor modulates the observed phenotypic characteristics. Ecophysiological investigation of Coffea genotypes in different environments revealed distinct responses, influenced by both light conditions and genetic characteristics. The results of biometric measurements indicated that the shaded environment promoted an increase in leaf area and etiolation of the genotypes, while the full sun environment favored a greater stem diameter and length of plagiotropic branches. The analysis of chlorophyll a fluorescence parameters was sufficient to reveal ecophysiological differences between the genotypes grown in the shade. With genotypes in full sun presenting the best photochemical performances. Specifically, under shaded conditions, the Arabica Arara and Conilon 10 genotypes presented, respectively, the best and worst photochemical performance. These results provide valuable insights into the genetic diversity and understanding of the morphophysiological adaptation of Coffea genotypes in different cultivation environments.